2003
DOI: 10.1086/376497
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Radio:X‐Ray Emission in the Hard States of Galactic Microquasars

Abstract: We present results of our study of correlated radio and X-ray emission in two black hole candidates and Galactic microquasars GRS 1915+105 and Cyg X-1 in their steady long term hard states, along with Cyg X-3 (using data obtained from Rossi X-Ray Timing Explorer all-sky monitor [RXTE-ASM], Compton Gamma Ray Observatory Burst and Transient Source Experiment [CGRO-BATSE], and Green Bank Intereferometer [GBI]). We detect a pivotal behavior in the X-ray spectrum of GRS 1915+105, correlated to the radio emission. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Choudhury et al (2003) point out that correlation between the X-ray and radio emission and the anti-correlation between the soft and hard X-rays are directly related to a causal connection between the spectral shape in the X-rays and the radio emission. They have shown that such a picture consistently explains the observed behaviors of three bright Galactic X-ray binary sources Cygnus X-3, Cygnus X-1 and GRS 1915+105.…”
Section: X-ray Radio Correlationsmentioning
confidence: 93%
See 3 more Smart Citations
“…Choudhury et al (2003) point out that correlation between the X-ray and radio emission and the anti-correlation between the soft and hard X-rays are directly related to a causal connection between the spectral shape in the X-rays and the radio emission. They have shown that such a picture consistently explains the observed behaviors of three bright Galactic X-ray binary sources Cygnus X-3, Cygnus X-1 and GRS 1915+105.…”
Section: X-ray Radio Correlationsmentioning
confidence: 93%
“…This signifies a definite connection between the inflow of matter via accretion disk emission and the outflow via jet emission (Choudhury et al 2003).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The correlation between radio and Xray emission may also be interpreted within the framework of the Two Component Advective Flow (TCAF) model [47], in which the location of a boundary layer between the thin disk and the Comptonizing region determines the spectral shape and also the amount of outflow [48].…”
Section: Broadband Jet Emissionmentioning
confidence: 99%